ANALISIS KARAKTERISTIK HABITAT KEPITING BAKAU (Scylla spp.) DI EKOSISTEM MANGROVE KELURAHAN KANDANG KECAMATAN KAMPUNG MELAYU KOTA BENGKULU - Zamdial Zamdial; Dede Hartono; Ari Rhamadhon; Nurlaila Ervina Herliany (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2021)
The goals of this study was to identify the characteristics of mangrove crab habitat in Kandang Village, Kampung Melayu District, Bengkulu City. This research was conducted in September 2020, using a survey method. Primary data were collected by direct observation and measurement methods at the research location.The station for sampling and data measurement was determined by the purposive method. All samples were analyzed in the Fishery Laboratory, Faculty of Agriculture, Bengkulu University.The analysis of the bottom substrate type was carried out using the Shepard Triangle method. Macrozoobenthos data analysis was conducted to determine the conditions of structural community which consisted of diversity index (H '), uniformity index (E) and dominance index (C). The study results showed the waters parameter values of the mangrove crab habitat were temperature (290 C), pH (7), and salinity (10ppt). Based on sediment analysis showed that the sediment was dominated by the dust fraction, which was 74.54%, then followed by 11% clay and 10% sand. The substrate of the waters is a dusty clay type, with a composition of dust (74.54%), clay (11%), and sand (10%). There are 4 types of macrozoobenthos that found from substrate samples, namely Thiaridae, Corbiludae, Bulimidae, and Gobiidae. The value of the diversity index (H ') macrozoobenthos was 0.83 and the dominance index value (C) was 0.74. The uniformity index (E) was based on the calculation of the data obtained by the value of 0.60, this showed that the level of uniformity was high, also justified by the presence of one dominating individual. The parameter values and the type of water substrate in Kandang Village, Kampung Melayu District, Bengkulu City still support the growth and survival of mangrove crabs.